The Impact of Education and Training on Product–Service Design: The Moderation of Competitive Advantage - Yangailo, Tryson (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: This study attempted to investigate the impact of education and training on product-service design by including competitive advantage as a moderating variable to provide more insight into the nature of this relationship. Design/methodology/approach: A quantitative research approach was employed, and primary data was collected from TAZARA management employees. Model fit, reliability, and validity were tested using regression analysis, factor analysis, and principal component analysis using Jamovi software. Findings: The results of the study present a significant positive relationship between education and training and product-service design. The results also show that competitive advantage negatively moderates the relationship between education and training and product-service design. Practical implications: The study provides more insights by providing empirical evidence on the nature of the relationship between education and training and product-service design. It is important for organizations to foster a culture of continuous learning and innovation. Managers should communicate the importance of adapting to changes in the marketplace, even when a competitive advantage exists. Balancing the preservation of what makes the organization successful with an openness to new ideas is critical to long-term sustainability and continued success in product-service design. Paper type: Research paper